Assistance for logo rebranding and packaging "Dodol Lima Pandawa" to improve product quality - Trecy Austin; Lisdiana Lisdiana; Ardiansyah Ardiansyah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The use of online media in the process of selling products is intended to help the community more easily in terms of marketing in line with the post-Covid 19. The implementation of this community empowerment depends on the ability of the community or mothers who have small businesses in Tebing Gerinting Village, South Indralaya. One of the main pillars of the Indonesian economy is to develop small businesses in villages that are run directly by the local community without any third party. Villages are something that the government must raise in order to increase new independence for the community. The result of the implementation of this community empowerment activity is the competence of partners, namely being able to carry out good management strategies during the training. Universities provide full support to the community in Tebing Gerinting Village by carrying out implementation methods in the form of observation, formulation of dodol product planning, product branding assistance, dodol manufacture, and product marketing through online media Instagram, Facebook, and YouTube to improve product quality, and evaluation of product rebranding with a new name according to the story behind the product. The ultimate goal of this activity is to increase the profits of the Tebing Gerinting Village community and partners. The implementation of assistance related to productivity and product rebranding, insight into sustainable innovation, and activities by providing product sticker logos and product banners help partners to be known in the national market